Cultural aspects of the trees in selected European countries - Carvalho, Ana Maria (2011)
This publication is derived from the Outputs of Working Group One (WG3) of the EU COST ACTION E42 VALBRO with the contribution of Ana Maria Carvalho from ESA/IPB and CIMO to this theme in particular.